Presence of Hepatitis E Virus in a RED Deer (Cervus elaphus) Population in Central Italy. Issue 1 (19th April 2015) - Di Bartolo, I.; Ponterio, E.; Angeloni, G.; Morandi, F.; Ostanello, F.; Nicoloso, S.; Ruggeri, F. M.
Summary: Hepatitis E is an acute human disease caused by the hepatitis E virus (HEV). In addition to humans, HEV has been detected in several animal species and is recognized as a zoonotic pathogen. Pigs, wild boar and deer can be reservoir. In this study, we evaluated HEV prevalence in a free‐living red deer ( Cervus elaphus ) population in central Italy by detecting virus‐specific antibodies and RNA in sera. A total of 35 of 251 red deer sera were positive for anti‐HEV IgG. HEV RNA was detected in 10 of 91 sera examined. Two genomic fragments targeted by diagnostic PCRs in the capsid region were sequenced, both matching with genotype 3 HEV. Overall results confirmed the occurrence of HEV infection in deer also in Italy.